Structures of new C41 carotenoids produced using recombinant Escherichia coli expressing genes encoding isopentenyl pyrophosphate, methyltransferase, and carotenoid biosynthetic enzymes. Issue 51 (17th December 2020) - Takagi, Chiharu; Abe, Momoka; Kaneko, Yumi; Sasaki, Akane; Ito, Ayumi; Sakemi, Yuka; Maoka, Takashi; Breitenbach, Jürgen; Sandmann, Gerhard; Shindo, Kazutoshi
Graphical abstract: Highlights: We isolated the methylated carotenoids using chromatographic methods. We found 15- cis -phytoene, lycopene, β-carotene, zeaxanthin 16-methyl derivatives. MS, 1D, and 2D NMR analyses were used to identify these as all-new C41 carotenoids. Abstract: The production of methylated C41-C43 15- cis -phytoene, lycopene, β-carotene, and zeaxanthin using recombinant Escherichia coli that express the genes encoding isopentenyl pyrophosphate, C4-methyltransferase, and carotenoid biosynthetic enzymes, as well as the detection of their chemical structures using high-pressure liquid chromatography-mass spectroscopy (HPLC-MS) analyses have been previously reported. However, the positions of the methyl groups were not fully elucidated due to multiple possible sites that could be methylated. In this study, we have isolated the methylated carotenoids using chromatographic methods and unambiguously determined their structures as 16-methyl derivatives of 15- cis -phytoene, lycopene, β-carotene, and zeaxanthin via detailed MS, 1D, and 2D NMR analyses. These compounds were all identified as novel C41 carotenoids.